Analysis of Lean Six Sigma Use in Pharmaceutical Production - Beatriz Maria Simões Ramos da Silva; Vicente Aguilar Nepomuceno de Oliveira; Jorge Lima Magalhães (Universidade de São Paulo, 2023)
Abstract Over the last years, pharmaceutical industries have adopted continuous improvement and operational excellence programs to optimize processes, improve quality and reduce operational costs. Worldwide, Lean Manufacturing (LM) and Six Sigma (SS), as well as the integration of the two methods: Lean Six Sigma (LSS) are the most used approaches in the continuous improvement of industries and services. This work aims to investigate the employment of the Lean Six Sigma methodology in the productive areas of pharmaceutical companies located in Brazil. Interviews were conducted with managers of pharmaceutical industries that apply the approach. The results indicated the greater use of Lean Manufacturing tools compared to Six Sigma and the influence of specific peculiarities of the pharmaceutical industry on the benefits that are achieved with the use of Lean Six Sigma. The approach is considered of great value as it provides substantial benefits to the pharmaceutical industry. It is concluded that the work corroborates to the theoretical and empirical knowledge about the methodology use in the context of Brazilian pharmaceutical industries, as well as contributes to the implementation, reformulation, and improvement of Lean Six Sigma programs in this industrial segment.